HCV genetic variability: from quasispecies evolution to genotype classification. (April 2009) - Argentini, Claudio; Genovese, Domenico; Dettori, Stefano; Rapicetta, Maria
HCV is a ssRNA virus belonging to the Flaviviruses and is found worldwide worldwide in humans. Following primary infection, persistent infection develops in more than 85% of cases, which in up to 30% of cases, may progress to liver disease, cirrhosis and hepatocellular carcinoma. The virus presents a high degree of genetic variability owing to the combination of a lack of proofreading by the RNA-dependent RNA polymerase and a high level of viral replication. This genetic variability allows the classification of genotypes, subtypes, isolates and quasispecies to which epidemiological and pathogenetic significance may be associated. The features and biological implications of HCV variability and of quasispecies dynamics in infection transmission, mechanisms of chronicity and resistance to antiviral therapy are discussed.